Masterplots II. Poetry series. - Jason, Philip K., 1941-; Irons-Georges, Tracy (Pasadena, Calif. : Salem Press, 2002)
Comprehensive coverage of the most commonly studied poems written in or translated into English.
[v.] 1. "A"-Brief pause in the organ recital -- [v.] 2. Briggflatts-dreams of the animals -- [v.] 3. The drunken boat-heritage -- [v.] 4. Hero and leander-the listeners -- [v.] 5. Listening to the music of Arsenio Rodriguez-on my first son -- [v.] 6. On poetry: a rhapsody-sketch for an aesthetic project -- [v.] 7. Skipper Ireson's ride-translations -- [v.] 8. The translucent mechanics-zone, Indexes.
Rev. ed.: Masterplots two / Frank Northen Magill, 1992-1998.
Includes bibliographical references and indexes.
Keywords: Poetry -- Themes, motives